2009
DOI: 10.1016/j.dyepig.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Solid state tautomerism in 2-((phenylimino)methyl)naphthalene-1-ol

Abstract: The solid state tautomerism of 2-((phenylimino)methyl)naphthalene-1-ol was studied using X-ray measurements and absorption spectroscopy. In the solid state, the keto tautomer predominates. The observed shift in the equilibrium from the enol (dilute solution) to the keto (solid state) forms is explained by the formation of dye aggregates using ab initio quantum chemical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Currently, structural data for the enol and keto tautomers of 1 are available in the literature [18] along with data for the fixed enol tautomer (OMe compound) of 6 [69]. In the case of compounds 2 – 5 even if crystallographic data are available the structures contain contribution of both tautomers [70,71], which makes the structural information unsuitable for benchmarking.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, structural data for the enol and keto tautomers of 1 are available in the literature [18] along with data for the fixed enol tautomer (OMe compound) of 6 [69]. In the case of compounds 2 – 5 even if crystallographic data are available the structures contain contribution of both tautomers [70,71], which makes the structural information unsuitable for benchmarking.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with recent work on similar compounds. 27 Table 2 reports the relative Gibbs free energies (∆G) and the activation barriers (∆G q ) calculated for a temperature of 298.15 K for the E / K equilibrium, as well as the values of the imaginary frequencies associated with the transition states. Both in the gas phase and in solution, the small energy differences and activation barriers indicate the coexistence of the E and K forms at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The main geometrical features (distances and dihedral angles) of the two tautomeric forms and transition state, as optimized in the gas phase and in solvent at the B3LYP/6-311G(d) level, are listed in Table S1 (Supporting Information). Theoretical values are compared to X-ray data of the N -(2-hydroxynaphthylidene)aniline compound, in which the NMe 2 group has been replaced by an H atom . The last line of Table S1 reports the bond length alternation (BLA), defined as ( d 14−4 + d N−17 − 2 d N−14 )/2, as an indicator for the strength of the electron delocalization along the compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Several theoretical and experimental studies on the azo-hydrazone tautomeric equilibrium can be found in the literature. However, due to the dependence of the tautomeric forms on the surrounding chemical environment, their structural and spectroscopic characterizations are not trivial. Indeed, many issues concerning the relative stability of these species and related with the intramolecular proton transfer that interconvert them into each other remain unclear.…”
Section: Introductionmentioning
confidence: 99%